Impact of Eloping on Household Life in the Community of Pota Village Sambi Rampas District, Manggarai Timur Regency - Naitboho, Yanti Rosalina (Universitas Muhammadiyah Yogyakarta, 2022)
This research focuses on two problem formulations concerning the practice of wa'a rai (elopement) carried out by the people of the Pota village and the factors that cause elopement, and the impact of elopement on domestic life. The research used descriptive and qualitative methods through field research. To facilitate the collection of data, facts, and information, the researcher will reveal and explain the problems in this study about how the impact of elopement on the household life of elopement actors after marriage in the Pota village community. Based on the analysis, it can be concluded that the practice of elopement in the Pota village community is allowed if it does not conflict with applicable law (Islamic Law and Law No. 4 of 1974). The elopement in the Pota village community is caused by internal and external factors. Internal factors include the absence of parental consent, mutual liking, and women having conceived out of wedlock. In contrast, external factors include Belis (dowry) and religious differences. The impacts of elopement in domestic life include economic or financial problems, triggering domestic violence, conflicts between daughter or son-in-law and parents-in-law, infidelity, and great opportunities for divorce.